2007
DOI: 10.1203/pdr.0b013e3180a02e50
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Medication During Pregnancy: Does Fetal Genotype Affect Outcome?

Abstract: Congenital abnormalities and impaired development in childhood are attributable to fetal exposure to antiepileptic drugs (AEDs). Pregnancy registries set up to obtain information about the potential risks of fetal exposure to AEDs, in particular major congenital malformations (MCMs), suggest that valproate exposure increases the frequency of congenital malformations more than other AEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 80 publications
0
24
0
12
Order By: Relevance
“…T his may be especially important for VPA since VPA exposure increases the frequency of congenital malformations more than other AEDs (ref. 41 ). At least one prospective observational study suggested that higher doses of VPA may significantly increase the risk of major malformations 42 .…”
Section: Discussionmentioning
confidence: 99%
“…T his may be especially important for VPA since VPA exposure increases the frequency of congenital malformations more than other AEDs (ref. 41 ). At least one prospective observational study suggested that higher doses of VPA may significantly increase the risk of major malformations 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also revealed that intrauterine exposure of CBZ is associated with spina bifida [114] and neuro developmental problems [115] of human embryo when gravidas were exposed to CBZ monotherapy. Atkinson et al [116] also reported higher fetal losses and congenital malformation rates among women who were prescribed carbamazepine during pregnancy. Because the residue of CBZ in drinking water may provide a pathway to embryo and infant via intrauterine exposure or breast-feeding, the presence of CBZ in groundwater, and drinking water remains a significant concern warranting further systematic risk assessment studies.…”
Section: Toxicological Effectsmentioning
confidence: 96%
“…The placenta is obviously considered the crucial organ responsible for successful ontogeny. Evidence strongly suggests that the placenta expresses a range of transporters which are capable of controlling the transplacental dispositions of many toxicant agents, thereby playing a crucial role in fetal protection against maternal toxins (Myllynen et al, 2005Ceckova et al, 2006;Atkinson et al, 2007;Behravan and Piquette-Miller, 2007;Myren et al, 2007;Vahakangas and Myllynen, 2009;Prouillac and Lecoeur, 2010;Ni and Mao, 2011;Iqbal et al, 2012). Of main interest are the ATPbinding cassette (ABC) transporters, particularly the P-glycoprotein (P-gp) and the breast cancer resistance protein (BCRP), which are most intensively studied currently.…”
Section: Introductionmentioning
confidence: 99%